Enhancing Mathematics Achievement through Virtual Manipulatives: A Meta-Analysis of K–9 Intervention - Lisda Fitriana Masitoh; Enggar Prasetyawan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Virtual manipulatives (VMs) have emerged as innovative tools in mathematics education, yet their overall effectiveness remains unclear. This study aims to synthesize existing evidence on the impact of VMs on K–9 students’ mathematics achievement. A meta-analysis was conducted following PRISMA guidelines. A systematic literature search identified 23 experimental studies published between 2012 and 2022 that investigated the effectiveness of VMs in mathematics learning. Inclusion criteria required studies to provide sufficient statistical data and include control groups using either traditional methods or concrete manipulatives. Data were analyzed using the random-effects model via OpenMEE, and moderator analyses were performed based on education level and control group type. The overall effect size was strong and statistically significant (Cohen’s d = 1.603, 95% CI [0.881, 2.324], p 0.001), indicating that VMs significantly improve mathematics achievement. Subgroup analyses revealed larger effects at the secondary level (d = 1.810) than at the primary level (d = 1.280), and greater effectiveness when compared to traditional methods (d = 1.979) than to concrete manipulatives (d = 1.473). Despite some heterogeneity (I² = 97.95%), publication bias was not evident. Findings affirm that VMs are effective tools for enhancing mathematics achievement across K–9 settings. Educators are encouraged to integrate VMs, especially in secondary classrooms. Further research should explore long-term impacts and broader contextual variables.